Prediction of lower extremities' movement by angle-angle diagrams and neural networks - Kutilek, Patrik; Farkasova, Barbora (Acta of bioengineering and biomechanics, 2011)
In contemporary science, the analysis of human walking is extensively used. The prediction of leg motion, as well as rehabilitation, can be usable for orthosis and prosthesis programing. Our work is focused on predicting of human walking by angle-angle diagrams, also called cyclograms. The applications of cyclograms in conjunction with artificial intelligence offers wide area of applications in medicine. But until now, this approach has not been studied or applied in practice.
Keywords: bioinženýrství; analýza hlavních komponent; biomechanika; Leg; lidé; infračervené záření; Models, Biological; Walking; Ankle; Hip; chůze; koleno; bérec; kyčel; Humans; Knee; Principal Component Analysis; Infrared Rays; biologické modely; Biomechanical Phenomena; neuronové sítě; Neural Networks, Computer; Bioengineering; kotník